Estimating the Indicator of Labour Efficiency in Conditions of Digital Transformation - Zh. V. Andreeva (Вестник Российского экономического университета имени Г. В. Плеханова)
In global economic science there is no uniform approach to interpretation of such notions as efficiency and labour productivity, therefore problems with their reading are possible. Through analyzing the research findings the author identified the scheme of correlation between the ideas of efficiency, labour productivity and quality of work. The article proposes criteria for estimating labour efficiency in view of two categories: labour productivity and quality of work. It is shown that quality of work is made up by two characteristics: quality of work organization at the enterprise, which includes appraisal of effectiveness of workers’ labour within the frames of enterprise functioning and quality of working life, which includes assessment of working conditions at the enterprise. The author elaborated an approach to estimating principle criteria, which gives an opportunity to assess labour efficiency at the enterprise by using a number of indicators that are acute in conditions of digital transformation and thanks to this, it is possible to get more reliable results and optimize processes in the organization. Using estimation of indicators of labour productivity and quality of work it can be possible to rank the level of enterprise maturity and identify measures aimed at raising efficiency of work.